Borderlands: The new mestiza - Anzaldúa, Gloria (Spinsters, Aunt Lute, 1987)
Rooted in Gloria Anzaldúa’s experience as a Chicana, a lesbian, an activist, and a writer, the groundbreaking essays and poems in this volume profoundly challenged how we think about identity. Borderlands/La Frontera remapped our understanding of what a “border” is, seeing it not as a simple divide between here and there, us and them, but as a psychic, social, and cultural terrain that we inhabit, and that inhabits all of us. This twentieth-anniversary edition features new commentaries from prominent activists, artists, and teachers on the legacy of Gloria Anzaldúa’s visionary work
Le texte « La conciencia de la mestiza : Toward a New Consciousness » a été donné en lecture au cours POL4212.
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; féminisme décolonial; identités LGBTQIA2+; lit3220; littérature; mexique; pol4212; premier cycle; queer; régions géographiques; thématiques; états-unis; études littéraires

La lettre aérienne - Brossard, Nicole (Les éditions du remue-ménage, 1985)
Lieu d’invention, laboratoire où s’élaborent une pensée originale et la recherche d’un langage inédit, La lettre aérienne rassemble douze essais de Nicole Brossard écrits entre 1975 et 1985. Ces textes témoignent de la quête individuelle de l’écrivaine, ancrée dans l’histoire, dans l’affirmation de la modernité québécoise et l’émergence d’une culture affranchie de la norme patriarcale.
Keywords: amériques; approches et analyses; arts; cours; discipline; fem1000; identités; identités LGBTQIA2+; lesbianisme; lit3495; littérature; premier cycle; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires